Synergistic effects of voting and enforcement on internalized motivation to cooperate in a resource dilemma - Daniel A. DeCaro; Marco A. Janssen; Allen Lee (Judgment and Decision Making, 2015)
We used psychological methods to investigate how two prominent interventions, participatory decision making and enforcement, influence voluntary cooperation in a common-pool resource dilemma. Groups (N=40) harvested resources from a shared resource pool. Individuals in the Voted-Enforce condition voted on conservation rules and could use economic sanctions to enforce them. In other conditions, individuals could not vote (Imposed-Enforce condition), lacked enforcement (Voted condition), or both (Imposed condition). Cooperation was strongest in the Voted-Enforce condition (Phase 2). Moreover, these groups continued to cooperate voluntarily after enforcement was removed later in the experiment. Cooperation was weakest in the Imposed-Enforce condition and degraded after enforcement ceased. Thus, enforcement improved voluntary cooperation only when individuals voted. Perceptions of procedural justice, self-determination, and security were highest in the Voted-Enforced condition. These factors (legitimacy, security) increased voluntary cooperation by promoting rule acceptance and internalized motivation. Voted-Enforce participants also felt closer to one another (i.e., self-other merging), further contributing to their cooperation. Neither voting nor enforcement produced these sustained psychological conditions alone. Voting lacked security without enforcement (Voted condition), so the individuals who disliked the rule (i.e., the losing voters) pillaged the resource. Enforcement lacked legitimacy without voting (Imposed-Enforce condition), so it crowded out internal reasons for cooperation. Governance interventions should carefully promote security without stifling fundamental needs (e.g., procedural justice) or undermining internal motives for cooperation.